Bioethical Aspects of Health Judicialization for drugs in 13 Municipalities in the Midwest of Santa Catarina, Brazil - Zago, Bruna; Mayumi Swiech, Liliane; Bonamigo, Elcio Luiz; Schlemper Junior, Bruno Rodolfo (Acta Bioethica, 2016)
Health´s judicialization is a recent phenomenon in Brazil, with serious repercussions for the Brazilian public health system. The aim of this work was to study its occurrence in thirteen small towns in the Midwest of Santa Catarina, southern Brazil, in the period of 2007-2012, analyze bioethical issues related and propose solutions. The results showed that, in this period, the total value/year of lawsuits by drugs increased almost 10 times, benefiting only 175 patients, or 0.134% of 129,497 inhabitants, at a cost of R$ 1.484.389,92 (US$ 740,000). Therefore, it can be inferred that the principle of autonomy of these patients and physician, committed, intensely, the equity and fair distribution of the scarce resources. It was concluded that this phenomenon, in the study area, has many features similar with those of large urban centers, has been unfair from the point of view of bioethical principles and also that the implementation of an Intermunicipal Committee of Bioethics could act as a mentor and educator in the careful definition of autonomy, fairness and justice in the allocation of scarce resources of health. Further studies are needed to assess the consequences of health´s judicialization nationally and find solutions more ethically appropriate.